Distinct Skin Microbiota Imbalance and Responses to Clinical Treatment in Children With Atopic Dermatitis - Liu, Ying; Wang, Shan; Dai, Wenkui; Liang, Yuan; Shen, Chunping; Li, Yunzhu; Jiao, Lei; Bian, Yawei; Gao, Zhan; Li, Yinhu; Li, Dongfang; Li, Shuaicheng; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Background： Atopic dermatitis (AD) is a common cutaneous disease in childhood, associated with imbalances in the skin microbiota. Objective： To explore the characteristics of the cutaneous microbiota and its dynamic changes during clinical treatment in AD patients. Methods Cutaneous swab samples were collected from 51 AD patients for 16S rDNA analysis before treatment, and 40 AD patients remained for cutaneous sample collection after a two-week treatment with mometasone and mupirocin. In parallel, 31 healthy children (HC) each were enrolled to collect a single swab sample. Results： At baseline, compared with HC, AD patients exhibited significant enrichments of Prevotella and Desulfovibrio as well as obvious reductions of Corynebacterium, Streptococcus and Parabacteroides. Based on the proportion of Staphylococcus aureus in the baseline skin microbiota, the AD patients were further classified into S. aureus-predominant group (AD.S) and S. aureus-non-dominant (AD.ND) group. At baseline, the AD.S group exhibited lower skin microbial diversity (P<0.001, Wilcoxon rank sum test) and higher atopic dermatitis (SCORAD) index (P=0.002, Wilcoxon rank sum test) than the AD.ND group. After two weeks’ treatment, the SCORAD index in both groups was significantly decreased. In the AD.S group, the cutaneous microbial diversity significantly increased from 2.9±0.8 (Mean±SD) to 3.7±1.0 (P=0.016, FDR=0.016, Wilcoxon signed-rank test), while the relative abundance of S. aureus decreased from 42.5±20.7 to 10.3±28.4 after treatment (P=0.014, FDR=0.666, Wilcoxon signed-rank test). In contrast, no significant skin microbiota changes were detected in the AD.ND group. Conclusions： AD patients with predominant S. aureus in the skin microbiota had higher disease severity and lower microbiota diversity compared to patients in the AD.ND group. Mometasone and mupirocin therapy had significant effects on skin microbiota in AD.S patients, including reduced S. aureus abundance and increased microbiota diversity, but had a paradoxical response in the AD.ND patients.